2012
DOI: 10.1186/1743-8977-9-24
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particulate matter on inflammatory markers in the general adult population

Abstract: BackgroundParticulate air pollution is associated with increased risk of cardiovascular disease and stroke. Although the precise mechanisms underlying this association are still unclear, the induction of systemic inflammation following particle inhalation represents a plausible mechanistic pathway.MethodsWe used baseline data from the CoLaus Study including 6183 adult participants residing in Lausanne, Switzerland. We analyzed the association of short-term exposure to PM10 (on the day of examination visit) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 45 publications
(48 reference statements)
9
70
1
3
Order By: Relevance
“…Although increased circulating cytokines have been postulated to cause a systemic response after PM exposure (Tsai et al, 2012), our data do not support the contribution of cytokines such as IL-6 in O 3 -induced metabolic impairment. Lipocalin levels were increased after acute O 3 exposure but this increase was only noted after 2 days, again suggesting that this is not likely the cause of acute hyperglycemia and glucose intolerance.…”
Section: Discussioncontrasting
confidence: 99%
“…Although increased circulating cytokines have been postulated to cause a systemic response after PM exposure (Tsai et al, 2012), our data do not support the contribution of cytokines such as IL-6 in O 3 -induced metabolic impairment. Lipocalin levels were increased after acute O 3 exposure but this increase was only noted after 2 days, again suggesting that this is not likely the cause of acute hyperglycemia and glucose intolerance.…”
Section: Discussioncontrasting
confidence: 99%
“…The levels of worker exposure to PM and nicotine in the present study were comparable to exposure levels measured in hospitality venues prior to cigarette smoking bans (8–1375 µg/m 3 PM2.5; 5.8–14.4 µg/m 3 nicotine) 34 35. Numerous epidemiology studies have previously demonstrated associations between airborne PM and BC levels and adverse cardiopulmonary effects although the ambient concentrations were much lower than what was measured in the hookah bars in this study 36 37. One study, in particular, found adverse blood pressure changes associated with daily ambient exposures to BC concentrations that were approximately 1/2–1/3 of the indoor levels measured in this study 38…”
Section: Discussionsupporting
confidence: 74%
“…3 (p-value = 0.038). In the past, a broad range of studies revealed the central role of TNF-α in inflammatory responses (Tsai et al, 2012), but some studies suggest the other way. For example, many studies chose IL-6 and TNF-α as combined biomarkers for studying inflammatory responses.…”
Section: Oxidative Damage and Inflammatory Responsementioning
confidence: 99%